Propuesta de Turismo de Aventura deporte extremo: Parapente en el cerro Chuqui sector la Mandalá del cantón macará provincia de Loja - Masache Gualan, Erik Adrian (2018)
Macará is a canton who possess a great natural and cultural wealth that has not been exploited in the tourist field. Macará is the first canton of the province of Loja that practices extreme adventure sports such as paragliding, for this reason the importance of developing a research based on an adventurous tourism proposal such as extreme paragliding sport should be taken into consideration by assigning an emphasis establishing the following points of view: aesthetic, social, cultural and economic, exposing planned and controlled tourism as a real alternative to increase income for the community as a catalyst for the local economy in the long term. With the above mention criteria , the development of the present work has as a; general objective: "Design a proposal for extreme paragliding adventure tourism in the Chuqui sector, located in the Mandalá sector of the Macará province of Loja", and with its specific objectives, the first one consisting of: Carrying out the tourist diagnosis for the development of tourism adventure of extreme sports such as paragliding in the hill Chuqui sector the Mandalá del Cantón Macará Province of Loja, the analytical method was used to describe the environment of the current situation of the different tourist sites for which it was taken into account: the development plan and territorial planning 2015-2019 (PDyOT) of Macará and the matrix of Carla Ricaurte itself was developed that provided the information corresponding to the diagnosis together with the scientific method that I provide to know the internal and external problems of the canton. The information collected was recorded in descriptive sheets, summary and ranking of MINTUR tourist attractions through which the current status of the attractions and the hierarchy level could be assessed. My study consisted of interviews and applied surveys which served to establish a SWOT matrix analysis, to finally determine the strategic objectives for the proposal. In the second objective, the following was taking in to consideration: "To elaborate the proposal of extreme adventure sport paragliding in the hill chuqui sector the Mandalá of the canton Macará Province of Loja" here we used the descriptive method that allowed to detail in real form the tourist elements that make up our object of study together with the field work. The design of the adventure tourism proposal was formulated for which technological means were used, such as Adobe Photoshop photo editing programs, Paint 3D that allowed the design of the same, and for the signage, the MINTUR methodology was taken into account. Finally, the third objective consisted of: "Socializing the proposal of extreme adventure sport paragliding in the hill chuqui sector the Mandalá of the canton Macará Province of Loja" by using the technique of MARPP (Method of Rapid Analysis and Participatory Planning) included in its 3 Pre-phases, Execution 5 and Results that were fundamental for the development of the participation workshop where the proposal was exposed, conclusions and recommendations were obtained from the participants. As a result of the research carried out, the lack of tourist information on the main tracts was discovered, as well as the lack of support from the authorities linked to tourism for the promotion and dissemination of tourist attractions. The adventure tourism proposal extreme paragliding will contribute to the tourist growth of canton Macará and will become a factor of promotion and diffusion of the attractions of the tourist attractions as well as being a tourist destination to be visited by tourists who like to perform extreme sports, this would assist to improve the economic activity of the place and therefore the quality of life of its habitant. Finally, it is recommended to the Municipal GAD of canton Macará , the Tourism Unit of the Municipality of Macará and the MINTUR, to carry out training workshops for people involved in the tourist field and citizenship in general, such as the linkage of authorities and population to the creation of innovative tourist projects that will take possession of the canton Macará as a tourist destination to be visited, as well as the promotion and tourist diffusion aimed to assist in the enhancing and allocating the canton as a touristic destination of the Province of Loja as well as the Country.